ANALISIS PERBEDAAN VARIABILITAS KEUNTUNGAN SAHAM, AKTIVITAS PERDAGANGAN SAHAM DAN BID-ASK SPREAD SEBELUM DAN SESUDAH STOCK SPLIT - Purwo Adi Wibowo (Universitas Islam Nahdlatul Ulama Jepara, 2005)
AbstrakStock Split represent policy of public company to break one share sheet become n share sheet , according to factor split. This policy still become conundrum because economically not assign add value to company but empirical evidence show that market give reaction. This research aim to analyse influence of stock split to share return (measured with security retum variability), activity trading of share ( measured with trading volume activity) and bid-ask spread , seen from there are difference before and after announcement of stock split.P eriod of research during 1999 till 2004 with determination of sampel use method of p urposi1 ·e sampling. Amount of taken company as sampel 85 from 92 emiten. Seven emit en out of analysis because one emiten, its share was not be t ra nsactioned and six emiten delisting. S ek unda 1y data used to be to be obtained by documentation of I CM D and JSX S tatistic 4'hQua rte1: Technical analys is used fo r different test is w il coxon s ign rank test if dist ribution da tais not normal and e paired samples t test if data have normal dist ribution. While to test da ta d ist ribution used by kolmogoro v-smirnov test.Result of research show that there are not difference of SR V and bid-ask spread among perio d before and after announcement ( H 1 and HJ unprovable). TVA have difference among peri od bef ore and after announcement ( H 2 Pr oven). Kata kunci: Stock split. pair ed sampl es t test, wilcoxon s ign rank test, security return variability, and bid-ask spr ead .